REFORMA PARADIGMA HUKUM DI INDONESIA DALAM PERSPEKTIF SEJARAH (History Department, Semarang State University and Historian Society of Indonesia, 2013)
This paper studies the development of the legal thought in Indonesia, which was influenced by the results of intellectual contemplation, which is irrespectively from the condition of time surround it, not only its ideology but also politicization towards symbolism of the common law, as the embryo of a national law. However, in the reality, the law in Indonesia is much influenced by colonial law as the written law. After the reformation period, massive range of steps has been taken to replace or reduce abandoned Dutch colonial law. This suggests that the orientation and characteristic of legal thought in Indonesia cannot be separated from social origin, as a base discovery of legal theories which have traditional values in Indonesia. In judicial practice, it has arisen various decisions that regard to the public’s justice sense which is not just based on the only written law. Keywords: Characteristics, Shifting Thought, Indonesian Legal History Artikel ini mendeskripsikan perkembangan pemikiran hukum di Indonesia. Pemikiran hukum Indonesia dipengaruhi oleh hasil perenungan intelektual, yang tidak terlepas dari situasi zaman yang melingkupinya, baik ideologisasi maupun politisasi yang mengarah pada simbolisme hukum adat, sebagai embrio hukum nasional. Namun dalam kenyataannya hukum di Indonesia banyak dipengaruhi oleh hukum kolonial yaitu hukum yang tertulis. Setelah reformasi, berbagai langkah massif dilakukan untuk menggantikan atau mereduksi hukum yang di-tinggalkan kolonial Belanda. Hal ini menunjukkan bahwa orientasi dan karakteristik pemikiran hukum di Indonesia tidak dapat dilepaskan dengan asal usul sosial masyarakat, sebagai basis ditemukannya teori-teori hukum yang memiliki nilai tradisi ke-Indonesiaan. Dalam praktik peradilan telah muncul berbagai putusan yang memperhatikan rasa keadilan masyarakat tidak sekedar berdasar pada hukum tertulis saja. Kata Kunci: Karakteristik, Pergeseran Pemikiran, Sejarah Hukum Indonesia